Penerapan Model Pembelajaran Cooperative Script dalam Memahami Materi Teks Fabel - Mandawa Putri, Maharani; Septyanti, Elvrin; Zulhafizh, Zulhafizh (UIR PRESS, 2023)
This study aims to find out how students understand the material by using the cooperative script learning model in fable text material for class VII students of SMPN 3 Bangko Pusako. The sample in the study was 60 students of class VII using the Total Sampling Design technique used was a one-group pretest-posttest design. In this study there were two groups, namely the experimental group and the control group. Data collection techniques used tests. Data analysis techniques using the normality test, homogeneity test and t test. To test the hypothesis used t test, from the calculation results obtained a significant level of 0.005. It turns out that the significance value (2-tailed) is 0.000 <0.05, so that H0 is rejected and H1 is accepted so that it can be concluded that there is significant influence and difference in the use of the cooperative script learning model in fable text material.